2022
DOI: 10.1007/s10916-022-01799-y
|View full text |Cite
|
Sign up to set email alerts
|

Online Mindfulness Experience for Emotional Support to Healthcare staff in times of Covid-19

Abstract: During the first confinement in Spain, between the months of March to June 2020, Information and Communication Technologies strategies were implemented in order to support health workers in the Wellbeing of Mental Health. Faced with so much uncertainty about the pandemic, an Online Mindfulness course. The objective of the course was to support healthcare professionals in Castilla y León in managing stress, anxiety and other emotional disturbances generated by coping with a situation as uncertain and unexpected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
0
10
0
1
Order By: Relevance
“…However, there are other areas of research that can contribute to suicide prevention. All of them contribute to the knowledge of this problem, for example, we can mention initiatives that help prevent it, such as training activities for its professionals (Castillo-Sanchez et al, 2019 ) and mindfulness therapies in times of COVID (Castillo-Sánchez et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are other areas of research that can contribute to suicide prevention. All of them contribute to the knowledge of this problem, for example, we can mention initiatives that help prevent it, such as training activities for its professionals (Castillo-Sanchez et al, 2019 ) and mindfulness therapies in times of COVID (Castillo-Sánchez et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of listening to understand were for those listening as well as those being heard. This practice took the pressure off individuals to fix another's problem or provide a solution but gave them direction about how to respond to distress: "I think I have become a better listener and, just ways of trying to encourage people to open up and share their experiences and let themselves, let them be vulnerable without being judged" (14). Through this practice participants learned how to resist their tendency to give answers: "they just let people be sad, and held the space by keeping their quietness, nobody tried to solve or give an answer" (12).…”
Section: Listening To Understandmentioning
confidence: 99%
“…You weren't being judged, you weren't going to say anything wrong, and they valued your input. So, it just made you want to open up more and be part of it (14).…”
Section: Creating a Safe And Healing Spacementioning
confidence: 99%
“…These principles have been described as relevant for managing the stressors during the pandemic [ 14 ]. However, few workplace programs to enhance HCW resilience and recovery have been identified or evaluated [ 15 , 16 , 17 , 18 ], and no studies to date have examined health workplace responses to a co-occurring natural disaster and pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the pandemic, workplace wellness initiatives typically focused on individuals addressing their own lifestyle risk factors, such as diet and exercise, outside of the workplace [ 29 ]. A few studies during COVID-19 examined the feasibility, acceptability, and effectiveness of interventions aimed at wellness and resilience of healthcare staff [ 15 , 16 , 30 ]. These studies found high satisfaction amongst participating staff and increased self-reported resilience [ 30 ].…”
Section: Introductionmentioning
confidence: 99%